Phagocytosis and oxidative burst by neutrophils in patients with recurrent furunculosis - ERGUN, SAFİYE ATLAS TÜLİN (My University, 1998)
Neutrophil phagocytosis of fluorescently labelled Staphylococcus aureus and oxidative burst by the neutrophils were assessed by flow cytometry in 22 patients with recurrent furunculosis and in 17 controls. Phagocytosis and oxidative burst were not found to be significantly different between the patients and controls. Low serum iron concentrations were demonstrated in six patients (27%). In these patients with hypoferraemia, oxidative burst was significantly lower than in the patients without hypoferraemia and in the controls. These data suggest that hypoferraemia may be an important predisposing factor in a subgroup of patients with recurrent furunculosis in impairing oxidative killing by neutrophils.